2011
DOI: 10.1074/jbc.m110.200295
|View full text |Cite
|
Sign up to set email alerts
|

Class II Phosphoinositide 3-Kinase Regulates Exocytosis of Insulin Granules in Pancreatic β Cells

Abstract: Phosphoinositide 3-kinases (PI3Ks) are critical regulators of pancreatic β cell mass and survival, whereas their involvement in insulin secretion is more controversial. Furthermore, of the different PI3Ks, the class II isoforms were detected in β cells, although their role is still not well understood. Here we show that down-regulation of the class II PI3K isoform PI3K-C2α specifically impairs insulin granule exocytosis in rat insulinoma cells without affecting insulin content, the number of insulin granules a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 54 publications
3
116
1
Order By: Relevance
“…PI3KC2␣ was found to regulate exocytosis of insulin in pancreatic beta cells (370), but was also activated by insulin via the small GTP binding protein TC10 (970) and played a role in insulin-induced Glut4 translocation (370). A role of PI3K-C2␣ was also suggested in neurosecretion (1034), and in this context, it is notable that TC10 was recently found to regulate axon cone specification by inducing translocation of the exo70 exocyst complex to membranes (391).…”
Section: Class II Pi 3-kinases/pi3kc2smentioning
confidence: 99%
See 3 more Smart Citations
“…PI3KC2␣ was found to regulate exocytosis of insulin in pancreatic beta cells (370), but was also activated by insulin via the small GTP binding protein TC10 (970) and played a role in insulin-induced Glut4 translocation (370). A role of PI3K-C2␣ was also suggested in neurosecretion (1034), and in this context, it is notable that TC10 was recently found to regulate axon cone specification by inducing translocation of the exo70 exocyst complex to membranes (391).…”
Section: Class II Pi 3-kinases/pi3kc2smentioning
confidence: 99%
“…PI3KC2␥ was claimed to play a role in regenerating liver (1171), but there is little knowledge concerning the involvement of this enzyme in any biological process. As pointed out above, it is increasingly evident that class II PI 3-kinases make PtdIns3P as their signaling molecule (370,970,1700). If the enzyme indeed makes primarily PtdIns3P, it is likely that it does so in very specific molecular contexts that differ from those regulated by the class III Vps34 enzymes.…”
Section: Class II Pi 3-kinases/pi3kc2smentioning
confidence: 99%
See 2 more Smart Citations
“…Leibiger and colleagues showed that PI3K-C2 is able to enhance glucose-stimulated insulin release in a feed-forward (126) mechanism, in response to stimuli from insulin itself, via the activation of PKB by PI3P. Subsequently, it was shown that PI3K-C2 may have a role in the late stages of insulin granule release through its action on the synaptosomal-associated protein of 25 kDA (SNAP25), which is independent of nutrient control (130). Insulin granules dock at the plasma mebrane via the interaction of SNAP25 within a protein complex (161)(162)(163), with granule fusion and insulin release occuring post proteolysis of SNAP25 (164).…”
Section: Pi3ks and Insulin Secretionmentioning
confidence: 99%